2016
DOI: 10.1152/ajprenal.00213.2016
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CXC chemokines in urine noninvasively discriminate OAB from UTI

Abstract: Overlapping symptoms of overactive bladder (OAB) and urinary tract infection (UTI) often complicate the diagnosis and contribute to overprescription of antibiotics. Inflammatory response is a shared characteristic of both UTI and OAB and here we hypothesized that molecular differences in inflammatory response seen in urine can help discriminate OAB from UTI. Subjects in the age range of (20-88 yr) of either sex were recruited for this urine analysis study. Urine specimens were available from 62 UTI patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 33 publications
0
43
0
Order By: Relevance
“…This current study restricted only to BPH patients negative for prostate cancer, as determined by prostate biopsy, found that increasing urine levels of CXCL‐10, CCL5, and CCL3 were marginally associated with the extent of inflammation and greater intensity of CD3 and CD20 lymphocytic infiltration in prostate tissue. Previous studies have reported that urine levels of CXCL‐10, CCL3, and CCL5 in healthy male asymptomatic control subjects are either undetectable or below the median values of BPH subjects reported here and elsewhere …”
Section: Discussionmentioning
confidence: 38%
See 3 more Smart Citations
“…This current study restricted only to BPH patients negative for prostate cancer, as determined by prostate biopsy, found that increasing urine levels of CXCL‐10, CCL5, and CCL3 were marginally associated with the extent of inflammation and greater intensity of CD3 and CD20 lymphocytic infiltration in prostate tissue. Previous studies have reported that urine levels of CXCL‐10, CCL3, and CCL5 in healthy male asymptomatic control subjects are either undetectable or below the median values of BPH subjects reported here and elsewhere …”
Section: Discussionmentioning
confidence: 38%
“…Here, we noted that extent of prostatic inflammation in different biopsy cores of BPH patients was associated with the elevation of CXCL‐10 and the grade of inflammation was marginally with the elevated urine levels of CCL3. We have previously reported that elevated urine levels of CXCL‐10 are associated with acute and chronic inflammation in lower urinary tract . CCL3 and CCL2 were found elevated in expressed prostatic secretions of prostatitis patients .…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…NGF content in homogenized tissue was determined using commercially available NGF Emax® ImmunoAssay System ELISA Kit (Promega, Madison, WI, USA) according to the manufacturer’s instructions. Intercellular Adhesion Molecule-1 sICAM-1(Othumpangat et al, 2012a) and monocyte chemoattractant protein-1 (MCP-1)(Tyagi et al, 2016) were analyzed by Luminex xMAP kit obtained from EMD Millipore (Billerica, MA) as previously described and calculations were expressed as pg/mg of protein.…”
Section: Methodsmentioning
confidence: 99%